Physico-chemical properties and selected nutritional components of Wild Medlar (Vangueria Infausta) fruit harvested at two haevesting time - Mothapo, Matholo Joyce (University of Limpopo, 2014)
Wild medlar (Vangueria infausta subsp. infausta) is a popular indigenous fruit available and consumed by rural communities in Limpopo Province, South Africa. Inadequate post-harvest practices in indigenous fruit plants including V. infausta fruit forms major constrains in expanding their production. There is scanty information documented on neither objective nor subjective harvesting indices of indigenous fruit plants consumed by locals in sub-Saharan Africa. Thus, the objective of this study was to determine the effect of harvesting time on physico-chemical properties and selected nutritional composition of V. infausta fruit. Fruits were harvested twice, where two harvesting times were regarded as treatments and each tree as replication. The reduction for fruit weight, sugar content and sugar/acid ratio was highly significant (P ≤ 0.05), whereas for average fruit diameter, seed weight, acid ratio and pH content this may imply that the listed parameters are treatment which was non-significant (P ≤ 0.05). The treatment reduced P, K, Mn and Fe by 33%, 18%, 3% and 7%, respectively. On the other hand, treatments had no effect on N and Ca. The reduction of phosphorus was highly significant (P ≤ 0.05), whereas for N, K, Ca, Mn and Fe treatment impact was non-significant (P ≤ 0.05). Similarly, the treatment consistently reduced moisture content and increased dry matter and crude protein of V. infausta by 76%, 300% and 7%, respectively. The reduction of moisture content, increase in dry matter was highly significant (P ≤ 0.05), whereas crude protein treatment impact was non-significant (P ≤ 0.05). The data indicated that the best time to harvest V. infausta fruit was during January when fruits were cosmetically appealing and not wrinkled. This study demonstrated that there was less variation in some measured objective harvesting indices of V. infausta fruit harvested at two harvesting time. More work would be required to do physico-chemical properties and selected mineral elements analysis from wide growth habitat for conclusive recommendations.
Thesis (M.Sc. (Plant Production)) -- University of Limpopo, 2014
Keywords: Harvesting; Wild medlar; Harvesting -- South Africa -- Limpopo; Harvesting time; Fruit -- Harvesting; Wild medlar -- Harvesting